2017
DOI: 10.1186/s12943-017-0634-7
|View full text |Cite
|
Sign up to set email alerts
|

TRIM8 restores p53 tumour suppressor function by blunting N-MYC activity in chemo-resistant tumours

Abstract: BackgroundTRIM8 plays a key role in controlling the p53 molecular switch that sustains the transcriptional activation of cell cycle arrest genes and response to chemotherapeutic drugs. The mechanisms that regulate TRIM8, especially in cancers like clear cell Renal Cell Carcinoma (ccRCC) and colorectal cancer (CRC) where it is low expressed, are still unknown. However, recent studies suggest the potential involvement of some microRNAs belonging to miR-17-92 and its paralogous clusters, which could include TRIM8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 42 publications
0
47
1
Order By: Relevance
“…47 Mastropasqua et al, showed N-Myc dependent overexpressed miR-106b promoted chemoresistance via regulating of tripartite motif containing 8 (TRIM8) in colorectal cancer. 48 On the contrary, demonstrated miR-106b was downregulated in cisplatin-resistance lung cancer cell lines when compared with sensitive parental cells, 13 also forced overexpression of miR-106b was associated with increased sensitivity of cancer cells to cisplatin in testicular embryonal carcinoma. 49 Collectively, the studies discussed above indicated that miR-106b might have different effects on cellular processes including cellular progression and chemoresistance in various types of human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…47 Mastropasqua et al, showed N-Myc dependent overexpressed miR-106b promoted chemoresistance via regulating of tripartite motif containing 8 (TRIM8) in colorectal cancer. 48 On the contrary, demonstrated miR-106b was downregulated in cisplatin-resistance lung cancer cell lines when compared with sensitive parental cells, 13 also forced overexpression of miR-106b was associated with increased sensitivity of cancer cells to cisplatin in testicular embryonal carcinoma. 49 Collectively, the studies discussed above indicated that miR-106b might have different effects on cellular processes including cellular progression and chemoresistance in various types of human cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-suppressor protein p53 is important for cell function and genome integrity. 1 The decrease of p53 protein is a common feature of human malignant tumors, which leads to the deficiency of cell cycle detection point control and apoptosis induction. An enormous amount of research effort goes into small molecules that regulate p53, including wild-type repair of mutant p53 gene and interruption of the binding between p53 and an E3-ubiquitin ligase Mdm2 to prevent ubiquitination degradation of p53 and rescue the protein level of p53.…”
Section: Dear Editormentioning
confidence: 99%
“…In cancer research, Trim8 is down regulated in glioma affects cell proliferation and is associated with patient survival [24]. Trim8 also regulates stemness in glioblastoma through PIAS3-STAT3 [25] and inhibits tumour growth by restoring p53 tumour suppressor function through blunting of N-MYC activity in chemoresistant tumours [26]. In innate immunity under human non-alcoholic fatty liver disease and non-alcoholic steatohepatitis conditions, the function of Trim8 involves targeting of TAK1 to promote insulin resistance and steatohepatitis.…”
Section: The Effect Of Trim8 On Hepatic I/r Is Mediated By Tak1 Activitymentioning
confidence: 99%